Analyzing a novel organic substrate and fertilizer formulation for sustainable crop production - Fatima Eshun; Samuel Joe Acquah; Shine Francis Gbedemah; Richard Amfu-Otu; Michael Tuffour; Anthony Amoah (Discover Agriculture)
Abstract This study investigated the nutrient properties of four organic materials and a mixture of these four materials to ascertain their potential for the production of organic fertilizer and substrate. The organic materials are coconut husks (CH), corn leaves (CL), oil palm fiber (OP), and corn stem (CS), and their mixture is dubbed ‘CLOPS mixture’. Laboratory analysis was conducted to characterize these organic materials, thus testing for Nitrogen (N), Phosphorus (P), Potassium (K), Calcium (Ca), Magnesium (Mg), Sodium (Na), Sulphur (S), Zinc (Zn), Iron (Fe), Copper (Cu), Manganese (M), Organic carbon (OC) and Organic matter (OM). 200 g of each milled material was mixed to form one uniform mixture. The mixture and the individual materials were separately analyzed in the laboratory for their nutrient components. The standard method of wet digestion using 1:3 (HNO3:HCl) aqua regia for elemental analysis was adopted. The results show that these organic materials have good nutrients for plant growth. The nutrients recorded fall within the range and the CLOPS mixture recorded higher concentrations of Zn (23.64 mg/kg), OC (40.30%), and OM (69.31%). The study recommends the application of the CLOPS mixture to soils and as a substrate to enhance crop yield.